ANALISIS KANDUNGAN β-KAROTEN PADA JENIS SAWI PUTIH (Brassica pekinensia L) DAN JENIS SAWI HIJAU (Brassica Juncea L coss) SECARA SPEKTROFOTOMETRI UV-VIS - Sukmawati Syarif; Milka Flaning (Fakultas Farmasi UMI, 2013)
Analysis content of β-carotene for Sawi hijau (Brassica juncea L coss) and sawi putih (Brassica pekinensia L) By Spectrophotometri Visible. A heve applied of research about contentof β-carotene in two quality of sawi namely sawi hijau (Brassica juncea L coss) and sawi putih (Brassica pekinensia L). For to Analysis and senelles content β-carotene in sawi. Sawi sample to be extraction in demarcation by acetone. The result of extraction to extract agein with petroleum eter and applied safonification with KOH 15 %. Qualitative analysis applied with Chromatography method in thin layer using petroleum eter:Benzen (9:1). The result it showing there are spot which same on two samples and β-carotene pure as the compere. While Quantitative analysis with spectrofotometri visible using β-carotene pure as compere showing that the content of β-carotene sawi hiaju 99,23 mg/g and sawi putih 40,91 mg/g.Key Word : β-Karoten, Brassica pekinensia L, Brassica juncea L coss